Kenya Water Service Provider Creditworthiness Index Report - World Bank Group (World Bank, Washington, DC, 2016)
The Kenya water supply and sanitation (WSS) sector has been on a long path of facilitating commercial lending to Water Service Providers (WSPs). A key component of this effort is the evolution of rating the credit risk of WSPs for local lenders. However, the trade-off in credit rating WSPs is to provide the best credit analysis to help lenders assess the creditworthiness of WSPs, yet have a system that is simple and affordable enough to replicate on an annual basis. To solve this trade-off, the Water Services Regulatory Board (WASREB) and the Water and Sanitation Program of the World Bank have created a Creditworthiness Index for the WSPs in Kenya. In lieu of performing a full shadow rating analysis, which is much more thorough yet also more time-consuming and costly, the Creditworthiness Index provides a simplified snapshot of the financial and operational performance of WSPs.